Antioxidant Activity and Preliminary Determination of Major Compounds from Selected Rhodophyta and Ochrophyte Macroalgae from Colombia (2023)
ABSTRACT: Among the vast worldwide marine biodiversity, macroalgae could be the most suitable source for bioprospection and sustainable development due to the great availability in the sea, leading to enough biomass production for different applications based on chemical compounds as raw materials for industries such as nutrition, medicine, agriculture and cosmetics. In order to build the basis for developing a sustainable use of Colombian macroalgae, a preliminary study of primary and secondary metabolites in several genus from Colombian coasts was carried out. This work included Gracilaria sp. and Acanthophora spicifera (Rhodophyta), and Sargassum c.f. ramifolium (Ochrophyta). NMR and FTIR spectroscopic techniques allowed to identify agar and carrageenan polysaccharides structures in Rhodophyta as well as fucoidan and alginate in Ochrophyta algae. Gas chromatography coupled to mass spectrometry was carried out to get the sterols and fatty acids profiles. By spectrophotometric semiquantitative complementary methods we describe and interpret the antioxidant properties of extracts obtained based on phenolic compounds determination, FRAP, DPPH, ORAC and ABTS assays. The content of antioxidants, the extraction and structural determination varied depending on the species. The structure of polysaccharides were consistent with previous reports from the genus studied. The species included in this study are underutilized seaweeds which need to be known to fulfill the pertinent information required to establish their commercial value as a contribution to add value for the local biodiversity available in Colombia.